The archaeology of knowledge and the field of dramatic discourse (2008)
I have taken my theme rather than my title from the philosophical discourses of Michel Foucault in his classic work. The Archaeology of Knowledge (1977). Foucault tries, rigorously and implacably, to contain the imperial study of this ancient and pre-historical field and discipline within the elastic limits of the history of ideas and the literary concept of the oeuvre. We know that archaeology as a concept and as a method is not a language as in the association of signs. It is at the same time a form of representation of a past in its longing for a settled, stable, laid down and abiding present and an anticipation of a future that is settled and ‘dead', yet real, perpetually haunting and compelling attention. As an intellectual empathizer with the field - cultural or archaeological -1 hope to bring in. within the framework of the history' of ideas, the value of preserved knowledge. I shall cite largely from literature, drama and history why archaeology will continue to be a dominant, if not a domineering conceptual science in the cause of our present century